Pre-Service Chemistry Teachers’ Preconceptions about Rare Earth Coordination Chemistry: Results from an Explorative Interview Study - Banu Kisworo; Ahmad Mudzakir; Liliasari; Anna Permanasari (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to identify students' preconceptions about rare earth coordination chemistry. The method used in this research is exploratory interviews. This research involved 25 pre-service chemistry teacher at a university in West Java Province, Indonesia. The collected data was analyzed using qualitative content analysis. The research results showed that 60% of students were able to identify electronic waste as a source of valuable metals, but others did not know that there were rare earth metals contained in it. As many as 32% know ionic liquids as environmentally friendly solvents, but the majority of students do not understand the physicochemical properties of ionic liquids and the interactions between ionic liquids and rare earth metals. As many as 8% of students were able to explain the reaction to form rare earth metal coordination compounds correctly, while only 4% were able to explain the concept of luminescence in these compounds. These findings indicate the need for coordination chemistry course design that accommodates students' learning needs and links them to relevant environmental contexts to improve students' understanding and systems thinking skills.